Analysis Taxpayer Compliance with the Submission of Article 21 Income Tax Returns according to the Average Effective Rate (TER) in Regulation No.58 of 2023 - Indah Kurniyawati; Moh. Rizal Budi Anggara; Uswatun Khasanah; Defirna Indah Safitri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the level of compliance of taxpayers in submitting tax returns (SPT). Income (PPh) article 21 period, compliance must be a key factor in the optimization of tax revenue and the success of tax administration and in the frame of simplifying the calculation of withholding income tax rates (PPh) 21 month, the Government has issued PP No.58/2023. This study is to analyze the level of taxpayer compliance with the submission of Income Tax Article 21 tax returns according to the period with the purpose of the Average Effective Rate (TER) in PP 58/2023 To determine the difference in the level of compliance with the calculation of the use of the old and new rates in accordance with Article 21 of PP 58/2023. Article 2 paragraph (4) of PP 58/2023 regulates categories A, B and C in the TER classification with reference to the Non-Taxable Income (PTKP) group. The average Effective Rate (TER), which is 44 TER for category A, 40 TER for category B, and 41 TER for category C. The purpose of this study is to determine whether there is a difference in the level of tax payment compliance with the old and new utilization rates in accordance with Article 21 of PP 58/2023. Comparative descriptive qualitative analysis, which describes and compares data from two or more research results with various approaches, was used in this study. This research shows that the application of this TER does not increase the burden of income tax article 21. The difference from the old calculation is only to help taxpayers simplify their tax calculations.